ANALISIS KEDUDUKAN KEUANGAN NEGARA DALAM BUMN YANG TELAH DIPRIVATISASI - WAFDANSYAH ANGGI HUSAINI; BISMAR NASUTION; MAHMUL SIREGAR (TRANSPARENCY, 2013)
The problem related to the privatization of  State–Owned  Corporations  is as  an urgent  issue  recently. It is as the effect of nationality assets as the target of  privatization   which is frequently  debated as the  existence of the  policy to  sell some  state owned    corporations for the  foreigners.  In other words,  the problem occurs in the  privatization  of State Owned  Corporations  as the  impact of  government policy  without  considering the needs of the  people in general.  The problem to raise  in this  thesis is  related to rule governing  the privatization  of State Owned  Corporations, legal aspects  of  state  financial in privatization  of State Owned  Corporations, and the state financial condition  in  State Owned  Corporations  which  have been  privatized. The method used in this research was   normative  yuridical.  Normative research  method was also called as  doctrinal research, that is   the research  to analyze  law either  law as it is  written in the book  or  law  it is decided  by the  judge through  judicial process.  Normative  law research   was   based on  secondary data  and  emphasized  on  the  steps of  speculative-theoretical  and normative-quantitative  analysis. The privatization program is intended to  increase the performance and  valued-added of the company  as well as to add the participation of the people  in  the possession of  company  shares. The privatization was done  by paying attention on the  principles of  transparencies,  self-support,  accountability,  responsibility,  and  reasonably.  The privatization  can be done  by  selling  shares  based on  capital market clauses,  share  direct selling for  investors,  and  share selling for  management and/or related employees.  State financial  in  State Owned  Corporations   is as  different wealthy from the   wealthy of  state and with  the rights to  get profit  from  the results of the company.  The  wealthy of the state  in  one State Owned  Corporation  depends  on the  type of the corporations.  If  the type of  State Owned  Corporations are  in   Public  Company, then all  capital  shall be  owned to  state. However,  if it is in the form of  limited company,  then partly of the capital  (at least  51%)   shall be as the  asset of  state  and it  is  divided on the  shares. State Owned  Corporations  which  have been  privatized in fact shall transfer  partly of state  shares  (represented by  government)  on the state  financial  in  State Owned  Corporations  which  have been  privatized to private  parties and the  possession of shares will be smaller than  50%.  It means  that  new investors  as  the holder   of shares  in State Owned  Corporations  which  have been  privatized  may  get  partly of shares in State Owned  Corporations.  As the  biggest  shareholders,  new investors  shall try hard  and  efficiently  to get optimal profit,  absorb  new  workers  and  give more contribution  for the  government  through  tax payment  and   dividend  division. Key words  :  State  Financial,  State   Owned  Corporation,  Privatization